Time year one [videorecording (DVD)] - Bean, Sean; Graham, Stephen, 1973-; Finneran, Siobhan, 1967- (BBC Studios, 2021)
Mark Cobden is a husband and father like any other. Except that he's responsible for the death of an innocent man. Tortured by visions of his victim, Mark welcomes his four-year sentence as penance for his crime. But in this brutal environment, a former teacher is an easy target for the more ruthless residents. Eric McNally is a dedicated prison officer, doing his best to protect those in his charge. And in an understaffed prison that's brimming with tension, the inmates' safety rests on a knife-edge. When a dangerous convict threatens to hurt someone Eric loves, this honest man faces an impossible choice.